Walls of Resistance: Graffiti, Language, and Student Protest in the July Movement at Dhaka University - Md Sabbir Hossain (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2026)
AbstractUniversity campuses are important sites of student protest, yet limited attention has been paid to how multilingual graffiti functions as political discourse within campus movements. This study examines graffiti produced during the July Movement at Dhaka University to determine how linguistic and semiotic choices shaped political expression, student identity, and activism. Using a qualitative design, the study combines field observation, photographic documentation, content analysis of 18 graffiti samples from different campus locations, and interviews with eight students representing supportive, oppositional, and mixed views. The analysis focuses on borrowing, expression borrowing, code-switching, code-mixing, adaptation, morphological variation, and semiotic meaning across Bangla, English, Persian, Urdu, and Spanish. The findings show that graffiti transformed campus walls into a contested linguistic landscape through which students expressed resistance, solidarity, anger, satire, and collective memory. Code-switching and code-mixing connected local grievances with broader activist vocabularies, while borrowed and adapted expressions linked the movement to historical and transnational repertoires of resistance. The study contributes to protest-language and linguistic-landscape scholarship by demonstrating how multilingual campus graffiti makes activism visible, memorable, and politically contested. It concludes that graffiti should be understood as both a communicative resource and a site of struggle over meaning, identity, and public memory.